Genetic tracing of farmed shrimp (Decapoda, Penaeidae) in wild populations from a main aquaculture region in Mexico - Perez-Enriquez, Ricardo (2018)
Release or escapes of aquaculture organisms may impact the genetic composition and variability of wild populations, leading to diverse issues that may compromise long-term wild stock fitness. Therefore, it is relevant to determine if farmed stocks are currently interacting with wild populations. Shrimp farming is an aquaculture activity taking place along the tropical Pacific coast of the Americas, and represents the most important culture bussiness of Northwestern Mexico. In this study, wild and farmed whiteleg shrimp Litopenaeus vannamei from the State of Sinaloa were genetically evaluated to determine admixture levels. A newly developed set of 14 microsatellite markers (mean number of alleles per locus 11.8, and 0.836 expected heterozygosity) was obtained by Next Generation Sequencing to characterize samples. Sampling consisted of 32 wild shrimps collected during three years (2002, 2012, and 2013) and three different sites, and two hatchery stocks from 2007. No significant differences were observed among years in the wild samples, but cluster analyses showed that hatchery-produced individuals were different from wild specimens. Deviations from Hardy-Weinberg Equilibrium and genotype assignment tests indicated that a fraction from each sample could contain individuals from hatchery origin. Even though the estimated fraction of escaped farmed individuals in the most recent samples (2012-2013; mean = 7.1 %) is considered of low genetic risk, management recommendations for hatcheries and farms were provided. Besides, the reasons that explain the intended and unintended farmed shrimp release into the wild were discussed.